Innovative blood sugar monitoring in Karonsih, Semarang: Bridging comfort and accuracy - Hartono; Affa Ardhi Saputri; Sheilla Rully Anggita; Susilawati; Qisthi Fariyani; Jasuri; Ice Uliya Sari (Community Research and Application Journal (CRAJ), 2024)
This community service activity aimed to promote health awareness by measuring blood sugar levels among residents of Karonsih, Semarang, using both invasive and non-invasive methods. The project, led by the Physics Department of Universitas Islam Negeri Walisongo in collaboration with the Ngabdi Neliteni Ngabekti (N3) community organization, provided free blood sugar screenings to 19 residents, two of whom showed elevated blood sugar levels and received feedback on lifestyle modifications to help maintain healthy glucose levels. The non-invasive prototype blood sugar monitoring device used in this study showed an average error rate of 47.08% compared to standard invasive measurements, suggesting areas for improvement in accuracy. However, the resident's enthusiasm and the device's environmental benefits indicate the potential for further development. This project underlines the importance of community health education and highlights the role of innovative technology in creating accessible and sustainable health monitoring solutions.